UNVEILING AMMOTERE ABBAJI: EXPLORING SILARIANG PERPETRATORS WITH SER MATHEMATICAL MODELING AMONG THE BUGIS COMMUNITY IN SOUTH SULAWESI - Rudi; Annas, Suwardi; Side, Syafruddin; Pandjajangi, Andi Muhammad Ridho Yusuf Sainon Andi; Irwan (Journal of Mathematics, Computations and Statistics, 2024)
This study focuses on the mathematical SER model capturing the rate of Ammotere Abbaji Case Behavior among individuals associated with Silariang. Primary data is gathered through questionnaires administered directly to the community in South Sulawesi Province, shedding light on the pace of Ammotere Abbaji Case Behavior among those involved with Silariang. The research journey starts with the construction of the SER model, followed by an analysis and simulation of the Ammotere Abbaji Case Behavior among Silariang participants. This encompasses identifying equilibrium points, evaluating model stability, computing the basic reproduction number (R0), conducting model simulations using Maple software, and interpreting the simulation results. Within this article, the mathematical SER model emerges through the analytical lens and simulation of Ammotere Abbaji Case Behavior among Silariang participants. Two equilibrium points are discovered: the free equilibrium point of Ammotere Abbaji Case Behavior among Silariang participants, and the equilibrium point specific to this behavior. The calculated basic reproduction number R0=0.045 indicates a decrease in the population engaged in Ammotere Abbaji Case Behavior among Silariang participants.